Ontology of the accident: An essay on destructive plasticity - Malabou, Catherine (Cambridge Polity, 2012)
* Catherine Malabou is a rising star of French philosophy and has a high reputation in the English speaking world. This is the second of several books by her that Polity will publish, the first being Changing Difference.